Diseño de un modelo de gestión de mantenimiento para el Taller Electromecánico del Instituto Costarricense de Ferrocarriles (INCOFER) División Pacífico” - López-Abarca, Kendall (Instituto Tecnológico de Costa Rica, 2017)
Public transport is a fundamental piece in the field of urban mobility, in Costa Rica, the railroad has regained the attention of citizens as a viable alternative to move between the congested cities that make up the Great Metropolitan Area (GAM). However, since the reactivation of passenger service in 2005, the institution faces perhaps its most important challenge, which is to offer a quality service (continuous, efficient, timely and safe) despite the growing demand and shortage of services means. The Electromechanical Workshop plays a fundamental role, since the quality of services is directly influenced by the maintenance received by the equipment. Hence the importance of managing the human and economic resources of the organization in the best way possible, for this purpose it is necessary for the entity to have a road map, a plan. The purpose of this project is to lay the first stone in the construction of the path of continuous improvement; by proposing a maintenance management model that integrates the mission and vision of the institution, along with control mechanisms (COVENIN 2500-93 and indicators), process and cost management, and optimization of existing maintenance (PMO). All hand in hand with previous studies, to create a comprehensive overview of the maintenance organization.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2017.
Keywords: INCOFER; Gestión; PMO; Electromecánica; Mantenimiento; Research Subject Categories::TECHNOLOGY::Engineering mechanics